1970
DOI: 10.1029/ja075i034p07199
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial spreadF: Implications of VHF radar observations

Abstract: Scatter from field‐aligned irregularities associated with equatorial spread F has been studied using the powerful 50 MHz radar at Jicamarca. We find that these irregularities, which have a wavelength of 3 meters, first, at times can be generated anywhere in the F region, no matter with what vertical velocity the region is moving, second, have growth times of a few seconds or less, third, move at velocities comparable to that of the F layer, and fourth, may attain strengths of perhaps 107–108 times the backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
231
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(245 citation statements)
references
References 34 publications
8
231
0
Order By: Relevance
“…It is well-known that the height of the F -region ionosphere is the major parameter in controlling the onset of equatorial spread F (ESF) (Farley et al, 1970). This relationship is due to the fact that the growth rate for the generalized RayleighTaylor instability is inversely proportional to the ion-neutral collision frequency, which decreases exponentially with altitude (Kelley et al, 1979a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that the height of the F -region ionosphere is the major parameter in controlling the onset of equatorial spread F (ESF) (Farley et al, 1970). This relationship is due to the fact that the growth rate for the generalized RayleighTaylor instability is inversely proportional to the ion-neutral collision frequency, which decreases exponentially with altitude (Kelley et al, 1979a).…”
Section: Introductionmentioning
confidence: 99%
“…Hysell and Burcham (2002) divides the pre-sunrise ESF into two categories. The first, as described by Farley et al (1970) and MacDougall et al (1998), occur just before sunrise near the F peak. The other may be due to "dead bubbles".…”
Section: Equatorial Spread-fmentioning
confidence: 99%
“…Because the K p , D st , AU, AL indices are defined by the different magnetospheric and ionospheric currents one needs to decide which of these is the best indicator for predicting the equatorial scintillations. Comparing the VLF drift velocities and VHF scatter on the Jicamarca radar, the idea was suggested by Farley et al (1970) of a threshold height above which the F -layer has to go before irregularities associated with spread F can be generated. Basu et al (1977) proposed that the observed scintillation activity at the equator and patches of activity off the equator may perhaps be due to varying thickness of the layers of irregularities in the transionospheric propagation of the signal.…”
Section: Discussionmentioning
confidence: 99%
“…This rocket experiment along with the observations from a 50 MHz radar, provided the ®rst evidence that the regions of depleted plasma density rise due to a buoyancy force and attain altitudes far above the region unstable to the Rayleigh Taylor (RT ) instability. This partly explained the high altitude spread F, observed by Farley et al (1970), in terms of primary instability operating below the peak in F region electron density (F peak ). Costa and Kelley (1978) analyzed the bottom side electron density data, obtained from the same¯ight, and found that the steepened coherent structures exhibited shallow spectra, with k )2 power law behavior in intermediate (10 km > k > 100 m) and transitional (100 m > k > 10 m) scales instead of a turbulent cascade of structures.…”
Section: Introduction and Literature Reviewmentioning
confidence: 97%
“…Various radio, optical and in situ techniques have, therefore, been employed to understand di erent aspects of irregularities associated with ESF. Ground based observations of coherent VHF radar from Jicamarca (Farley et al, 1970) renewed the interest in this ®eld. The optical techniques which have contributed signi®cantly, include, all sky imagers and scanning photometers for measuring the zonal drift of large-scale irregularities (Mendillo and Baumgardener, 1982;Sinha et al, 1996, Taylor et al, 1997Tinsley et al, 1997, and references therein).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%